Progress in climate change adaptation in the Arctic. (26th August 2020) - Canosa, I V; Ford, J D; McDowell, G; Jones, J; Pearce, T
Abstract: Climate adaptation is a priority for Arctic regions which are witnessing some of the most rapid warming globally. Studies have documented examples of adaptation responses in the Arctic, but assessments evaluating if and how progress is being made over time remain scarce. We identify and examine adaptation progress in the Arctic using a systematic tracking methodology to compare adaptations documented during 2014–19 to those documented for the period 2004–2013 in a benchmark study by Ford et al (2014). Utilising the peer reviewed literature as out data source, we find no noticeable increase in reported adaptations across the two time periods, with the profile of adaptations undertaken remaining largely the same. The majority of documented adaptations continue to be reported in North America, are being undertaken most often in the subsistence-based hunting and fishing sector, are primarily developed in response to a combination of climatic and non-climatic stimuli, are reactive and behavioural in nature, and are mainly carried out at the individual/community scale. Climate change is observed, however, to have a more prominent role in motivating adaptation between 2014–19, consistent with intensifying climate-related exposures in the Arctic. There is limited evidence in the reported adaptations analysed that potential opportunities and benefits from the impacts of climate change are being targeted. The paper provides a general characterisation of adaptation across the Arctic and how it is evolving, and needs to be complimented in follow-up work by studies using alternative data sources on adaptation and research at national to regional scales.